Impact of lead concentration on linear and nonlinear optical parameters of amorphous chalcogenide Sn-Ge-Se system - M. M. Abd El Raheem; M. M. Wakkad; H. A. Mohamed; N. A. Hamed; H. F. Mohamed (Journal of Materials Science: Materials in Engineering)
Abstract Some physical properties of Sn5Ge10Se85-xPbx; (x = 2.5, 5, 10, 15 17.5 and 20 at. %) chalcogenide glasses, namely average coordination number (CN), deviation of stoichiometry (r), floppy modes (f), cross-linking density (X), average number of constraints (Ncon), lone pair electrons (Lp), overall mean bond energy ( < E˃), and average heat of atomization (Hs), are depicted. The experimental and theoretical values of the optical band gap E op for different contents of Pb were found to be very close to each other. The dispersion properties, such as complex dielectric function $$\widetilde{ε }$$ ε ~ , optical conductivity $${σ }_{op}$$ σ op , single oscillator E o, and dispersion energies E d, are investigated. On the other hand, electrical conductivity is studied. Our results are based on the Tauc equation, Wemple and Di-Domenico (WDD) model, Pankove method, Tichy and Ticha relationship, and Miller’s rule. The values of the first-order χ (1) and third-order χ (3) of optical susceptibility and the nonlinear refractive index (n 2) were found to increase with the increase of Pb content, which has a maximum value, hence decreasing thereafter with the increase of the latter.